Pendidikan Berbasis Nilai Mengintegrasikan Etika dan Moral Untuk Mencerdaskan Generasi Muda - Gofur, Muhamad Abdul; Huda, Miftahul; Hakim, Faishol; Suhartiningsih, Suhartiningsih (STAI Bani Saleh, 2025)
Education is one of the main pillars in shaping individual character and personality. In an increasingly complex globalization era, challenges in education lie not only in academic aspects but also in the development of moral and ethical values. Value-based education becomes essential to create a generation that is not only intellectually smart but also possesses good character and high social awareness. This research aims to explore and analyze how value-based education can be integrated with ethics and morals in the learning process to educate the younger generation. By understanding the relationship between value-based education and character development, it is hoped that more effective strategies for its implementation in schools can be found. The research method used is a qualitative approach with a case study design. This study involves data collection through in-depth interviews with educators and students, as well as document analysis related to the value-based education curriculum. The research population consists of several schools in various regions, with purposive sampling taken to obtain relevant and in-depth information. The results of the study indicate that value-based education has a positive impact on students' character development. The integration of moral values into the curriculum can enhance students' social awareness and empathy, as well as reduce negative behaviors among them. Furthermore, this research found that challenges in implementing value-based education are often caused by a lack of training for educators and support from school management. Thus, this research provides significant contributions to the development of better and sustainable education for the younger generation.